Testing of "Global Young's Modulus E" on a rehabilitated masonry bell tower in Venice. (August 2017) - Bergamo, Otello; Campione, Giuseppe; Russo, Gaetano; Motta, Elisa
Abstract: This paper shows the effectiveness of the techniques chosen for the rehabilitation of the historic "Sant'Andrea" masonry bell-tower in Venice. The achieved rehabilitation projects based on the so-indenting technique consisting in removing and replacing bricks in bad conditions, and on the isolation of the bells at the belfry quote, respect all the constraints represented by the aesthetic and structural features of the building. Moreover, the experimental analyses used to define the existing state of the structure are described in detail. The tower is also an interesting case study for the validation of the proposed method to determine the Global Young's Modulus in a rehabilitated masonry bell tower. Highlights: Experimental characterization of constituent material masonry bell tower Dynamic test for determination of modulus of elasticity Rehabilitation of bell tower with dynamic isolation of belts Rehabilitation indenting technique for masonry bricks